2009
DOI: 10.1016/j.exphem.2009.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Complex developmental patterns of histone modifications associated with the human β-globin switch in primary cells

Abstract: 1) Objective:The regulation of the β-globin switch remains undetermined and understanding this mechanism has important benefits for clinical and basic science. Histone modifications regulate gene expression and this study determines the presence of three important histone modifications across the β-globin locus in erythroblasts with different β-like globin expression profiles. Understanding the chromatin associated with weak γ gene expression in bone marrow cells is an important objective with the goal of ulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 45 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…24 Higher H3K9me2 at the fetal compared with the adult genes was also reported in primary human bone marrow erythroblasts in the absence of ex vivo culture. 28 Inhibition of G9a methyltransferase activity caused a strong decrease of H3K9 dimethylation throughout the locus, but this was especially notable at the g-globin gene promoter associated with reactivation of g-globin gene expression, further supporting a repressive role for G9a in regulation of hemoglobin production. Surprisingly, the decrease in H3K9 dimethylation at the adult globin gene promoters after UNC0638 treatment was associated with repression of these genes suggesting that H3K9me2 does not play a significant role in regulation of the adult b-globin genes.…”
Section: Discussionmentioning
confidence: 99%
“…24 Higher H3K9me2 at the fetal compared with the adult genes was also reported in primary human bone marrow erythroblasts in the absence of ex vivo culture. 28 Inhibition of G9a methyltransferase activity caused a strong decrease of H3K9 dimethylation throughout the locus, but this was especially notable at the g-globin gene promoter associated with reactivation of g-globin gene expression, further supporting a repressive role for G9a in regulation of hemoglobin production. Surprisingly, the decrease in H3K9 dimethylation at the adult globin gene promoters after UNC0638 treatment was associated with repression of these genes suggesting that H3K9me2 does not play a significant role in regulation of the adult b-globin genes.…”
Section: Discussionmentioning
confidence: 99%
“…However, even though these regions were identified as having conservation scores predictive of a cis-regulatory element, attempts to refine sites of GATA-1 binding by using in vitro binding with EMSA were unsuccessful, with no correlation between EMSA binding and PhastCons score. Numerous factors contribute to DNAprotein binding and subsequent erythrocyte gene expression, including cis sequences, concentration and stability of regulatory proteins, and chromatin architecture (7,10,35,37,41,55,58,61,64,99). It is likely that a complex combination of factors regulates GATA-1 binding to its cognate DNA binding site.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the establishment of methods allowing generation of a large quantity of embryonic globin-expressing erythroblasts from human embryonic stem cells (hESCs) lead to studies comparing the epigenetic landscapes of β globin locus of hESC-derived erythroid cells, FL, and bone marrow erythroblasts. It has been found that complex developmental patterns of histone modifications as well as the formation of extended DNA hypomethylation domains are associated with the human β-locus globin switch [7, 8]. In this study, we provide further evidence that a looping mechanism is associated with the expression of ε globin in these hESC-derived erythroblasts, just as it is associated with the expression of fetal γ globin in FL cells and the expression of adult β globin in adult peripheral blood (PB) CD34 + cells derived-erythroid cells.…”
Section: Introductionmentioning
confidence: 99%